Multidimensional poverty among social groups in Kerala : incidence, intensity and disparity - Baiju, K. C.; Sivaraman, Shibu (Cambridge Scholars Publishing, 2018)
This book narrates the living conditions and incidence of poverty among households belonging to the different social groups in Kerala, India. Using a micro-level study, it investigates the inter-group variations with regards to the incidence of multidimensional poverty in the sample area, the Kasaragod District, Kerala. The Regional Human Development Enabling Index (RHDEI) and the Multidimensional Poverty Index (MPI) are the main tools used for analysis here. The book highlights the incidence, intensity, and disparity of multidimensional poverty in Kerala, and clearly pinpoints the intra-state.